Adaptive Tourism as a Form of Socialization of Children and Adolescents with Autism Spectrum Disorders - S.N. Pantsyr; Y.V. Volodina (Moscow State University of Psychology and Education, 2022)
The need for the social adaptation of children and adolescents with autism spectrum disorders determined by its psychophysical development. The organization of basic and additional education of the presented category of chil dren should be carried out on the basis of adapted educational programs that consider specifics of child development. Adaptive tourism classes can fully apply to additional education programs. This direction includes a diverse list of areas of work with children, on the basis of which it is possible to make programs of special and developmental classes for children with ASD. One of the main directions is the development of socialization. Adaptive tourism programs, which include various effective teaching methods, contribute to the development of interpersonal relations, the for mation of group work skills, the development of behavioral peercommunication rules and norms, the development of leisure skills and successful adaptation in a children environment.